Gambaran Bahaya Dan Risiko K3 Dengan Metode HIRADC Pada Proyek Pembangunan Polder Pompa Sunter C Oleh PT. Nindya Karya Di Jakarta Utara Tahun 2025 (STIKES Columbia Asia Medan, 2026)
The Sunter C Polder/Pump construction project is a strategic effort to address flooding issues by increasing drainage system capacity. This project involves various high-risk construction activities that have the potential to cause workplace accidents and health issues. This study aims to identify hazards, assess risk levels, and determine control measures. The HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method involves a systematic identification of potential hazards at the project site, risk assessment based on impact and probability, and the formulation of appropriate control recommendations. This is a descriptive study designed to illustrate Occupational Health and Safety (OHS) hazards and risks, located at the Sunter C polder/pump construction project. The research was conducted from January to May 2025. Data were collected through interviews, observations, and information obtained directly from internal company documents. The results indicate that the application of the HIRADC method accurately identifies various primary hazards, such as the risk of falls, being struck by materials, chemical exposure, and ergonomic issues. The risk assessment suggests that most activities fall under the medium to high-risk categories, necessitating controls such as the use of Personal Protective Equipment (PPE), OHS training, and routine monitoring of working conditions. The implementation of the HIRADC method in this project is proven to enhance the culture of occupational health and safety and can serve as a reference for other construction projects in managing operational risks effectively.